Faecal calprotectin, lactoferrin, M2-pyruvate kinase and S100A12 in severe ulcerative colitis: a prospective multicentre comparison of predicting outcomes and monitoring response. Issue 9 (26th August 2010) - Turner, D; Leach, S T; Mack, D; Uusoue, K; McLernon, R; Hyams, J; Leleiko, N; Walters, T D; Crandall, W; Markowitz, J; Otley, A R; Griffiths, A M; et al.
Abstract : Objective: To compare four faecal markers for their ability to predict steroid refractoriness in severe paediatric ulcerative colitis (UC). Construct validity and responsiveness to change were also assessed. Methods: This was a prospective multicentre cohort study. Stool samples from 101 children (13.3±3.6 years; Pediatric UC Activity Index (PUCAI) at admission 72±12 points) were obtained at the third day of intravenous steroid therapy. Repeated samples at discharge were obtained from 24 children. Predictive validity was assessed using diagnostic utility statistics to predict steroid failure (ie, the need for salvage treatment). Concurrent validity was assessed using correlational analysis with the following constructs: PUCAI, Lindgren and Seo scores, physician's global assessment, albumin, erythrocyte sedimentation rate and C-reactive protein (CRP). Responsiveness was assessed using test utility and correlational strategies. Results: Median values (IQR) were very high at baseline for all four markers (calprotectin 4215 μg/g (2297–8808); lactoferrin 212 μg/g (114–328); M2-pyruvate kinase (M2-PK) 363 U/g (119–3104); and S100A12 469 μg/g (193–1112)). M2-PK was numerically superior to the other three markers and CRP in predicting response to corticosteroid treatment (area under the receiver operating characteristic (ROC) curve 0.75 (95% CI 0.64 to 0.85; p<0.001) vs <0.65 for the others). However, it did not add to the predictive ability of the PUCAI (area under the ROC 0.81 (95% CI 0.73 to 0.89)). M2-PK also had the highest construct validity but with a modest mean correlation with all constructs (r=0.3; p<0.05). None of the markers was responsive to change (Spearman's rho correlation with change in the PUCAI <0.1; p>0.05, area under the ROC curve <0.65; p>0.05). Conclusions: The four markers were greatly elevated in severe paediatric UC. Only M2-PK had good construct and predictive validity, and none was responsive to change. The PUCAI, a simple clinical index, performed better than the faecal markers in predicting outcome following a course of intravenous corticosteroids in severe UC.